2012
DOI: 10.1371/journal.pone.0046056
|View full text |Cite
|
Sign up to set email alerts
|

Cryptic Diversity in the Ubiquist Species Parisotoma notabilis (Collembola, Isotomidae): A Long-Used Chimeric Species?

Abstract: Parisotoma notabilis is the most common species of Collembola in Europe and is currently designated as ubiquist. This species has been extensively used in numerous studies and is considered as well characterized on a morphological ground. Despite the homogeneity of its morphology, the sequencing of the barcoding fragment (5′ end of COI) for several populations throughout Europe and North America revealed four distinct genetic lineages. The divergence found between these lineages was similar to the genetic dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(62 citation statements)
references
References 53 publications
2
59
1
Order By: Relevance
“…Even for species that had been barcoded at other sites, their sequences were different from those collected from identical morphological species at the study site (i.e., <90% of sequence similarity). These results support the huge and hidden diversity in Collembola shown in previous studies (e.g., Porco et al 2012aPorco et al , 2012bCicconardi et al 2013) and suggest the need for generating more reference sequences of this group, more extensively at our study site as well as in various other geographic regions. At present, the construction of a locally collected database for mtCOI and mt16S genes will be needed to identify collembolan species from metabarcoding data.…”
Section: Selectivity and Sensitivity Assessed Using Natural Communitysupporting
confidence: 91%
See 1 more Smart Citation
“…Even for species that had been barcoded at other sites, their sequences were different from those collected from identical morphological species at the study site (i.e., <90% of sequence similarity). These results support the huge and hidden diversity in Collembola shown in previous studies (e.g., Porco et al 2012aPorco et al , 2012bCicconardi et al 2013) and suggest the need for generating more reference sequences of this group, more extensively at our study site as well as in various other geographic regions. At present, the construction of a locally collected database for mtCOI and mt16S genes will be needed to identify collembolan species from metabarcoding data.…”
Section: Selectivity and Sensitivity Assessed Using Natural Communitysupporting
confidence: 91%
“…Additionally, DNA barcoding (Hebert et al 2003) of Collembola, using a standardized portion of the mitochondrial cytochrome c oxidase subunit 1 (mtCOI) gene, revealed that cryptic species were frequently found among morphologically identical specimens from different regions (e.g., Porco et al 2012b), suggesting that conventional microscopic examination has confounded different species and underestimated their biodiversity. However, due to the required time and cost, it has not been practical to sequence every specimen by Sanger sequencing in community assessments where it is required to examine numerous microarthropods extracted from soil samples; typically, a 100 mL of bulk sample contains 100-1000 total animal specimens, including 10-30 species of Collembola (e.g., Takeda 1987).…”
Section: Introductionmentioning
confidence: 99%
“…1 and 2), suggesting the likely presence of cryptic species. The specific status of many of these lineages has, in fact, already been confirmed through supplemental molecular or morphological analysis (King et al 2008;Pérez-Losada et al 2009;James et al 2010;Porco et al 2012). This high discrimination power has sometimes been considered problematic (Armstrong …”
Section: Barcode Efficiency and Its Relevance For Monitoring Soil Invmentioning
confidence: 89%
“…The soil invertebrate fauna, highly important to the overall performance of terrestrial ecosystems, but also highly complex due to minute size, hidden lifestyle, and extreme diversity, is represented with about 4% (nematodes) to 16% (collembolans) of the described German species. While the standard mitochondrial COI barcode marker is widely used for animal taxa, the soil organisms section also included the nuclear 28S rRNA gene to confirm COI results as suggested by, e.g., Porco et al (2012), and to widen resolution efficiency, as in some taxonomic groups, the 28S marker proved more efficient for separation of closely related species and for amplification efficiency due to partially poor performance of standard COI primers.…”
Section: Completion Of the Reference Librarymentioning
confidence: 99%